2013
DOI: 10.1146/annurev-physchem-040412-110146
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Photochemistry in Liquids

Abstract: Ultrafast photochemical processes can occur in parallel with the relaxation of the optically populated excited state toward equilibrium. The latter involves both intra- and intermolecular modes, namely vibrational and solvent coordinates, and takes place on timescales ranging from a few tens of femtoseconds to up to hundreds of picoseconds, depending on the system. As a consequence, the reaction dynamics can substantially differ from those usually measured with slower photoinduced processes occurring from equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
165
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(174 citation statements)
references
References 173 publications
(166 reference statements)
7
165
0
2
Order By: Relevance
“…Moreover, as photoinduced ET reactions are triggered by light, their mechanism and dynamics can now be investigated with an unprecedented time resolution. 3 Moreover, photoinduced ET processes play a key role in areas as important as solar energy conversion and storage, [4][5][6][7][8][9][10][11][12] or light induced DNA damage. [13][14][15] A thorough understanding of their mechanism and of the parameters that affect their dynamics is thus a conditio sine qua non for further progress.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as photoinduced ET reactions are triggered by light, their mechanism and dynamics can now be investigated with an unprecedented time resolution. 3 Moreover, photoinduced ET processes play a key role in areas as important as solar energy conversion and storage, [4][5][6][7][8][9][10][11][12] or light induced DNA damage. [13][14][15] A thorough understanding of their mechanism and of the parameters that affect their dynamics is thus a conditio sine qua non for further progress.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral width of these features decreases with increasing Δt, indicative of vibrational cooling of these S1 molecules. 2 A negative (henceforth termed bleach) feature is also present, centered around 375 nm. Since the UV/visible absorption band of NMP does not extend this far to the red, this feature is assigned to stimulated emission from the S1 electronic state.…”
Section: Experimental and Computational Methodlogymentioning
confidence: 99%
“…Such femto-to-nano-second time window corresponds to the dynamics of energy and electron transfer within and between molecules as well as local structural modifications. [3] Further- Microfluidics for Ultrafast Spectroscopy http://dx.doi.org/10.5772/64428 more, the high repetition rate and the development in matters of laser stability and detection system gives the ability to monitor the absorption changes of a single molecule out of a thousand (corresponding to changes of ~10 -4 OD) in less than a second of accumulation time. [4] With such setups, it is for example possible to trigger the charge separation in the Photosystem I protein complex and to follow the liberated electron as it progresses from one side of the protein to the other.…”
Section: Ultrafast Transient Absorption Spectroscopymentioning
confidence: 99%
“…Ultrafast transient spectroscopy is indeed used for a broad range of investigations: being sensitive to changes in absorption spectrum of the proteins, it is possible to collect data on local conformational deformations, electronic transitions and (low) vibrational modes of oscillation within molecules, intra and inter molecular energy and electron transfers, etc. [10] In the field of solar energy conversion for example, which is one of today's essential topic in our energy savvy societies, this technique allowed to better understand the conversion processes from light to consumable energy. In particular, the study of photosynthesis showed how the specific arrangement of pigment within larger protein structure either favor the absorption and passing of the photon energy, as it takes place in antennae systems, or favors the generation of a charge separated state, as it happens in photosynthetic reaction centers, [4,9] which results in the liberation of a high energy, and therefore usable, electron.…”
Section: Studying Biological Samplesmentioning
confidence: 99%